Morphological, Molecular and MALDI-TOF MS Identification of Bedbugs and Associated Wolbachia Species in Rural Senegal. Issue 3 (14th March 2022) - Ndiaye, El Hadji Ibrahima; Diatta, Georges; Diarra, Adama Zan; Berenger, Jean Michel; Bassene, Hubert; Mediannikov, Oleg; Bouganali, Charles; Sokhna, Cheikh; Parola, Philippe
Abstract: Bed bugs are known to carry several microorganisms. The purpose of this study was to assess the prevalence of bed bug infestation in two rural areas of Senegal and determine the species present in the population. A screening was conducted to detect some arthropod associated pathogenic bacteria in bed bugs and to evaluate the prevalence of endosymbiont carriage. One survey took place in 17 villages in Niakhar and two surveys in Dielmo and Ndiop and surroundings area in the same 20 villages. Bed bugs collected were identified morphologically and by MALDI-TOF MS tools. Microorganisms screening was performed by qPCR and confirmed by sequencing. During the survey in the Niakhar region, only one household 1/255 (0.4%) in the village of Ngayokhem was found infested by bed bugs. In a monitoring survey of the surroundings of Dielmo and Ndiop area, high prevalence was found during the two rounds of surveys in 65/314 (21%) in 16/20 villages (January–March) and 93/351 (26%) in 19/20 villages (December). All bed bugs were morphologically identified as the species Cimex hemipterus, of which 285/1, 637 (17%) were randomly selected for MALDI-TOF MS analysis and bacteria screening. Among the Bacteria tested only Wolbachia (Alphaproteobacteria, Rickettsiales, Rickettsiaceae) DNA was found in 248/276 (90%) of the bedbugs. We briefly describe a high level of non-generalized bed bug infestation in rural Senegal and the diversity of Wolbachia strains carried by C. hemipterus . This study opens perspectives for raising household awareness of bed bug infestations and possibilities for appropriate control.